Enfermedades del fríjol causadas por virus y su control [conjunto audiotutorial] - Ospina O., Héctor Fabio; Gálvez E., Guillermo E.; Cárdenas A., Moisés; Castaño J., Mauricio; Flor Montoya, Carlos A. (International Center for Tropical Agriculture, 1979)
This audiotutorial unit (cassette, printed script, 124 color slides, study guide, self-evaluation test), prepared by the Communications Support Unit at CIAT, is available for use with a manually or automatically synchronized slide projector/cassette tape recorder. Each unit is available from the Distribution Office at a cost of US$$50; photocopies of the study guide alone can be obtained from the Bean Information Center. Among the diseases of beans, those caused by viruses are the most important, not only for the damage they cause (10-90 percent losses) but also because they are difficult to control since they are transmitted by insect vectors. Those transmitted by aphids (mainly Myzus persicae) are BCMV and BYMV; Bemisia tabaci transmits BGMV and bean chlorotic mottle virus; chrysomelid-transmitted viruses are bean rugose mosaic, southern mosaic and yellow mottle. Symptoms, geographic distribution, etiology, hosts and control are discussed. (CIAT)